Tingkat Ketahanan Pangan Rumah Tangga Petani Sebelum dan Selama Pandemi Covid 19 Di Desa Gohong Kabupaten Pulang Pisau - Novia Wulandari; Emmy Uthanya Antang; Betrixia Barbara; Evi Feronika; Masliani (LPPM Universitas Palangka Raya, 2021)
Pulang Pisau Regency has a total consumption of rice that 1.140 kcal/capita/day, less than the standard calorie intake of 2.200 kcal/capita/day. This study aimed to determine the level of household food security before and during the Covid-19 pandemic in Gohong Village, Pulang Pisau regency. This research was conducted in Gohong Village, Pulang Pisau Regency. Purposive selection of the location. Research conducted for 3 (three) months starting from October to December 2020. The number of samples was taken 20 households, the method used in determining the sample was the proportional simple random sampling technique. The data collected includes primary and secondary data. The analysis tools used is the share of food expenditure and energy adequacy. The results showed that the level of energy consumption from rice in the household was on average 888.46 calories/person/day, only reaching 44.42% of the energy adequacy of 2,000 calories/person/day. 25% of the household can achieve energy sufficiency from grains. 40% households were in the Food Expenditure Share above 60% before the Covid 19 Pandemic, and 35% households were in the Covid 19 Pandemic. 15% households were in food secure before the Pandemic it increased to 20% while Pandemic Covid 19. Increment in the number of households food secure was due to the decrease in the number of households with a Food Expenditure Share above 60%. The number of households on criteria food insecure before the pandemic was 85% consisting of 10% vulnerable, 45% lack of food, and 30% food insecurity. Meanwhile, during the pandemic, 80% of households were on the criteria food insecure, consisting of 5% vulnerable food, 45% lack of food, and 30% food insecure